2006
DOI: 10.2225/vol9-issue4-fulltext-6
|View full text |Cite
|
Sign up to set email alerts
|

Production and stability studies of the bioemulsifier obtained from a new strain of Candida glabrata UCP 1002

Abstract: Evaluation of both tenso-active and emulsifying activities indicated that a biosurfactant was produced by the newly isolated and promising strain Candida glabrata isolated from mangrove sediments. The extracellular water-soluble emulsifying agent was isolated and identified as a heteropolymer. The maximum of bioemulsifier production was observed when the strain was grown on soluble and insoluble substrates cotton seed oil plus glucose, reaching values *Corresponding author of 10.0 g/l after 144 hrs at 200 rpm.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 13 publications
0
17
0
1
Order By: Relevance
“…Biosurfactant production by Candida species has been reported previously (Shepherd et al 1995;Garcia-Ochoa and Casas 1999;Paraszkiewicz et al 2002;Sarubbo et al 2006). Sarubbo et al (2006) demonstrated that the biosurfactant produced by Candida glabrata when cultured in an n-hexadecane was not recovered from the culture fluid until after the organism entered the stationary growth phase, indicating the molecule was a growth dissociated product. The exact reasons why some microorganisms produce biosurfactants is still not clear.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Biosurfactant production by Candida species has been reported previously (Shepherd et al 1995;Garcia-Ochoa and Casas 1999;Paraszkiewicz et al 2002;Sarubbo et al 2006). Sarubbo et al (2006) demonstrated that the biosurfactant produced by Candida glabrata when cultured in an n-hexadecane was not recovered from the culture fluid until after the organism entered the stationary growth phase, indicating the molecule was a growth dissociated product. The exact reasons why some microorganisms produce biosurfactants is still not clear.…”
Section: Discussionmentioning
confidence: 80%
“…They have several advantages over their synthetic counterparts, such as lower toxicity, higher biodegradability (Zajic et al 1977), better environmental compatibility (Georgiou et al 1992), higher foaming (Razafindralambo et al 1996), high selectivity and specific activity at extreme temperature, pH and salinity (Velikong and Kosaric 1993;Ilori and Amund 2001;Ilori et al 2005;Sarubbo et al 2006), and the ability to be synthesized from renewable feedstock (Desai and Banat 1997). These unique properties allow the use of biosurfactants and possible replacement of chemically-synthesized surfactants in a great number of industrial applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High yields in biosurfactants have been reached through the combination between a vegetable oil and carbohydrate as substrate (Santos et al, 2016). Regarding the use of waste frying vegetal oils, isolated or combined with a soluble substrate, promising results have been obtained in the last decades for Candida species in our laboratories (Sarubbo et al, 1999, 2001, 2006, 2007; Coimbra et al, 2009; Campos et al, 2014). Thus, waste frying oil and molasses were used as the insoluble and soluble carbon sources, respectively, while corn steep liquor was used as the nitrogen source.…”
Section: Resultsmentioning
confidence: 99%
“…The E24 (and E72) index is given as percentage of the height of emulsified layer divided by the total height of the liquid column (cm). The percentage of emulsification index calculated by using the following equation (12), E24 = Height of emulsion formed x 100/total height of solution. Centrifuged samples of incubated tubes of sterile LB were used as control for each test strain.…”
Section: Methodsmentioning
confidence: 99%